Food processing to reduce antinutrients in plant-based foods - Faizal, Farrah Adlina; Ahmad, Nurul Hawa; Yaacob, Jamilah Syafawati; Abdul Halim Lim, Sarina; Abd Rahim, Muhamad Hafiz (Universiti Putra Malaysia, 2023)
Antinutrients such as phytic acids, tannins, saponin, and enzyme inhibitors are phytochemicals that can decrease the bioavailability of micro- and macronutrients, thus causing them to be unavailable for absorptions in the digestive system. Antinutrients are a major concern especially in countries where plant-based commodities such as wheat, legumes, and cereals are staple foods, for the antinutrients can cause not only mineral deficiencies, but also lead to more serious health issues. Although various thermal and non-thermal processing methods such as cooking, boiling, and fermentation processes have been practiced to decrease the level of antinutrients, these processes may also undesirably influence the final products. More advanced practices, such as ozonation and cold plasma processing (CPP), have been applied to decrease the antinutrients without majorly affecting the physicochemical and nutritional aspects of the commodities post-processing. This review will cover the types of antinutrients that are commonly found in plants, and the available processing methods that can be used, either singly or in combination, to significantly decrease the antinutrients, thus rendering the foods safe for consumption.